The Basic Law of Human Stupidity: Unraveling the Dark Force Hindering Human Welfare and Happiness - Abia Abia; Agustina Viani; Jayanti Silaen; Jessie Anggraini; Wahyu Hidayattulloh (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
"The Basic Law of Human Stupidity" explores the deplorable state of human affairs throughout history and identifies a powerful yet unorganized group within the human race that perpetuates unnecessary troubles and miseries. This group, operating without leadership or regulations, functions in perfect unison, amplifying the detrimental effects of each member's actions. This book seeks to understand the nature, character, and behavior of this group, providing insights to neutralize its impact on human welfare and happiness. It is important to note that this work is not an exercise in cynicism or defeatism, but rather a constructive effort to shed light on and address a significant obstacle to human progress.